Textile traces. A functional approach to current instruments as a contribution to the study of archaeological assemblages (Northwest of Argentina) - López Campeny, Sara María Luisa; Mamondes, Silena; Urquiza, Silvana Valeria (Arqueología, 2023)
This work integrates a line of archaeological research focused on the pre-Hispanic indigenous textile practices, taking as a case study the area of the central plain and Mesopotamia of Santiago del Estero (Argentine), in late pre-Hispanic and early colonial times. The present study focused on an ethnoarchaeological approach to the textile tools (accessories for the loom and garment finishing) currently in use among the weaving communities of the Argentine Northwest, elaborated on raw materials (bone and wood) that were possibly available in the sites and periods studied. The purpose was to record and characterize a set of artifacts at different scales to link their life history with the traces left in their topography. The relevance and potentiality of starting from an actualist approach is highlighted, as a methodological framework for a stage prior to the archaeological site approach. This contributes to the construction of hypotheses and the exploration of independent contrasting indicators, allowing us to expand the available interpretive basis for archaeological materiality.